Surgical management of primary pancreatic neuroendocrine tumors - Johnston, Michael E. (J Gastrointest Oncol, 2020)
Pancreatic neuroendocrine tumors (PanNETs) are the second most common malignancy of the pancreas, and their incidence is increasing. PanNETs are a diverse group of diseases which range from benign to malignant, can be sporadic or associated with genetic mutations, and be functional or nonfunctional. In as much, the treatment and management of PanNETs can vary from a “Wait and See” approach to orthotopic liver transplantation (OLT). Despite this, surgical resection is still the primary treatment modality to achieve cure. This review focuses on the surgical management of PanNETs.